Taxonomy and control of Trichoderma hymenopellicola sp. nov. responsible for the first green mold disease on Hymenopellis raphanipes - Zeng, Xiang-Yu; Yuan, Xiao-Xiao; Peng, Ke-Qin; Pan, Yin-Tao; Tan, Ting-Jun; Wu, Nan; Tian, Feng-Hua (Frontiers in Microbiology, 2022)
Trichoderma spp. are a group of widespread fungi with important application in many aspects of human life, but they are also pathogens that cause green mold disease on mushrooms. During a survey of mushroom cultivation in Guizhou, China, five strains of Trichoderma from three different localities were isolated from soil in mushroom bags of Hymenopellis raphanipes. Typical morphology of having gregarious, reddish stromata and gregarious phialides and results of phylogenetic analyses based on a combined dataset of RPB2, TEF and ITS gene sequences demonstrated that these green-spored Trichoderma belong to a new taxon, Trichoderma hymenopellicola. Pathogenicity tests by covering fungal mycelial blocks or soil mixed with spore suspension to mushroom bags showed similar symptoms to those in the field, and the same fungal pathogen had been observed and re-isolated from these symptoms, which fulfil Koch’s postulates. Primary screening test of nine common fungicides indicating Prochloraz-manganese chloride complex and Propiconazole are the top two effective fungicides inhibiting the pathogen, whereas the former was further indicated as a suitable fungicide to control Trichoderma hymenopellicola, with high inhibition ratio to the pathogen and low toxicity to the mushroom.